Popełnienie przestępstwa jako przyczyna niegodności dziedziczenia w polskim prawie spadkowym - Kuźmicka-Sulikowska, Joanna (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
The considerations conducted in this article are centered around the exact nature of one of the grounds for judging the unworthiness of inheritance by the heir after the particular devisor, namely around the case where the heir has intentionally committed a serious offense against the testator which is a prerequisite for judging the inadmissibility of inheritance under Article 928 § 1 point 1 of the Polish Civil Code. The terms used in the above of criminal law must be used here, especially in the context of the notion crime, its stadia and phenomena, as well as the intentional nature of the heirs actions. It has also been showned the need for an individual judgment in each case by the court whether the act can be classified as severe; the text comprises indications in this regard, including these flowing from the case law. To several of the above-mentioned aspects the author made some critical remarks, proposing her own interpretation of the discused regulations. Finally, the case of committing an offense as a reason for the ruling on the unworthiness of inheritance Article 928 § 1 point 1 of the Polish Civil Code has been compared to situations where this constitutes a ground for disinheritance Article 1008 point 2 of the Polish Civil Code. At this background some de legeferenda remarks has been made.
Keywords: dziedziczenie; niegodność dziedziczenia; sytuacja spadkobiercy; przestępstwo; niegodność dziedziczenia z tytułu dziedziczenia